The'ulama of Farangi Mahall and Islamic culture in South Asia - Robinson, Francis (London : C. Hurst, 2001)
Introduction--Perso-Islamic Culture in India from the Seventeenth to the Early Twentieth Century--Scholarship and Mysticism in Early Eighteenth-Century Awadh--The'Ulama of Farangi Mahall and Their Adab--Problems in the History of the Farangi Mahall Family of Learned and Holy Men--Al-Nizamiyya: A Group of Lucknow Intellectuals in the Early Twentieth Century--'Abd al-Bari and the Events of January 1926--'Ulama, Sufis and Colonial Rule in North India and Indonesia--Ottomans-Safawids-Mughals: Shared Knowledge and Connective Systems--Glossary--Index
Includes index : page 257-267.
Keywords: Firangi Mahall (Lucknow, India) -- History; Ulama -- South Asia; Islamic education -- South Asia -- History